Anxiolytic-Like Effect of Cymbopogon Citratus (Lemongrass) Essential Oil - Alvarado-García, Paul Alan Arkin (2023)
Introduction: Essential oils are complex substances that are widely utilized in the practices of aromatherapy. Certain essential oils are recognized for their potential to alleviate anxiety symptoms. This research was conducted to evaluate the effects of Cymbopogon citratus essential oil on anxiety. Methods: The chemical composition of the extracted essential oil was analyzed using Gas chromatography with flame-ionization detection (GC-FID) and Gas chromatography-mass spectrometry (GC–MS). In addition, an experimental study with measures at pretest-posttest was conducted, where 128 participants were divided into two groups, a waiting-list (WL) control group, and an experimental group (EG)treated with aromatherapy based on Cymbopogon citratus essential oil. The anxiety index was evaluated by Zung Self- Rating Anxiety Scale (SAS). Results: The chemical analysis identified geranial (52,1%) and neral (35,2%) as the principal constituents. Anxiety levels decreased in the experimental group during the posttest phase (p<0.05). Besides a large effect size was found for anxiety (d = 0.962; Δ= 0.988) with 1-β=0.999 a percentage of change of -10.99%. Conclusion: Cymbopogon citratus essential oil inhalation showed to be effective in decreasing scores anxiety. Therefore, it has the potential to serve as a supplementary treatment for anxiety.